Implementation of the PjBL model to enhance problem solving skill and skill competency of community college student - Nizwardi Jalinus; Rahmat Azis Nabawi (Jurnal Pendidikan Vokasi, 2017)
The research aims at enhance problem solving ability and competency skills of students. The method used was classroom action research in the course of welding practice with a group of 10 students. The research data obtained from the problem solving skills assessment interview techniques, competency skills gained from the project assessment and a written test, and the improvement data were analyzed using average gain (g). PjBL model provides students the opportunity to solve the problems of the real world by creating innovative works through their project work. PjBL model provides opportunities and experiences for students to solve the problem so the next project the students already have experience and ability to make decisions about what effort needs to be done to solve the problem. The power of thinking ability in solving the problem implications for increasing student competency skills, because any problems found can be resolved properly so that the process and the work of students increased for the better. From these results be obtained conclude the implementation of project based learning models can enhance the problem solving ability and competency skills of students.